The Experience Disrupters - Halligan, B. (Brian) (MIT Sloan Management Review, 2020)
We're seeing a new species of disrupter emerging in our economy: experience disrupters. These organizations have great products but offer even better experiences, and they're successfully outmaneuvering their competition by excelling at this. In a nutshell, how they sell is why they win.